Pengaruh Investasi, Tenaga Kerja dan Inflasi Terhadap Nilai Produksi Pada Sektor Industri - Putri, Eggyta; Rastini, Komang (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2013)
Production values are influenced by investment, employment and inflation simultaneously and partially, this is the destination of research in small industry in Gianyar regency and to know the variables that affect dominant. Methods of data collection in this study using the method of documentation and direct observation notes, documents and some of the literature related to the research, obtained through the research library of the relevant agencies such as the Central Bureau of Statistics Province, Gianyar regency Statistics and the Department of Industry and Trade to support the analysis of the Gianyar regency. Multiple linear regression analysis is used as a technique to discuss the influence of investment, employment and the rate of inflation on the value of production in this study. The results show that investment, employment and inflation simultaneously significant effect on the value of production in a small industrial sector in Gianyar regency period 1995-2011. In partially positive and significant investment. The number of workers have no effect, while the inflation rate negatively affect the value of production in a small industrial sector in Gianyar regency period 1991-2011. The results of this study stated that the variable investment appeal has the effect of other variables in the domain.
Keywords: investasi; tenaga kerja; inflasi